Performance Analysis and Development of a Semiconductor Junction Rectifier with Multicolor Coding for Indoor Farm Applications. (18th October 2021) - Kanmani Ruby, E. D.; Umadevi, M.; Kanmani Pappa, C.; Edwin Santhkumar, W.; Janani, P.; Shanmugasundaram, P.
Abstract : This paper aims to build a smart lighting system with applications such as remote for controlling power supply and optimizing heat management in the metal body of the semiconductor diode and with a printed circuit board for agriculture. The semiconductor diode strips with multiple colors are lined up and configured as a LED lamp with proper casing and heat sink. It has a driver circuit with required power regulation that is able to control the intensity of light for photosynthesis and plant growth requirements. The system uses hydroponics to plant the water, thus decreasing the usage of fertilizers. The entire system is controlled remotely using necessary communication interface application.